2017
DOI: 10.5500/wjt.v7.i2.117
|View full text |Cite
|
Sign up to set email alerts
|

Intra-islet endothelial cell and β-cell crosstalk: Implication for islet cell transplantation

Abstract: The intra-islet microvasculature is a critical interface between the blood and islet endocrine cells governing a number of cellular and pathophysiological processes associated with the pancreatic tissue. A growing body of evidence indicates a strong functional and physical interdependency of β-cells with endothelial cells (ECs), the building blocks of islet microvasculature. Intra-islet ECs, actively regulate vascular permeability and appear to play a role in fine-tuning blood glucose sensing and regulation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 169 publications
1
32
0
Order By: Relevance
“…Yet, both are requirements that need to be met to understand factors contributing to regulatory mechanisms in the crosstalk of b-cells and ECs in the human body. 44 In this study, we identified three major spatial distributions of b-cells and ECs in native human pancreatic tissue: (1) the even distribution of both cell types, (2) ECs surrounded by b-cells, and (3) b-cells surrounded by ECs. We FIG.…”
Section: Spatial Distribution Of Heterotypic Pseudo-islet Cultures Simentioning
confidence: 99%
“…Yet, both are requirements that need to be met to understand factors contributing to regulatory mechanisms in the crosstalk of b-cells and ECs in the human body. 44 In this study, we identified three major spatial distributions of b-cells and ECs in native human pancreatic tissue: (1) the even distribution of both cell types, (2) ECs surrounded by b-cells, and (3) b-cells surrounded by ECs. We FIG.…”
Section: Spatial Distribution Of Heterotypic Pseudo-islet Cultures Simentioning
confidence: 99%
“…EVs and their associated noncoding RNAs are involved in the physiological cellular communication in endocrine organs. In the pancreas, EVs mediate the exchange of information between beta cells with endothelial cells and adjacent beta cells [ 129 , 130 ]. Through their RNA cargo, EVs regulate beta cell function, insulin secretion, and angiogenesis [ 131 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, EV-miRNA content varies based on cell conditions and EVs released by beta cells treated with proinflammatory cytokines were shown to lead to apoptosis of naive beta cells [ 129 ]. Besides the direct interaction between beta cells, the physiopathology of pancreatic islets has been demonstrated to depend on a crosstalk between beta cells and endothelial cells [ 130 ]. EVs seem to contribute to cell communication, and EVs isolated from human pancreatic islets were shown to be biologically active, inducing insulin mRNA expression, enhancement of angiogenesis, and protection from apoptosis.…”
Section: Metabolic Syndromementioning
confidence: 99%
“…IMECs are highly fenestrated which facilitates immediate detection of blood glucose levels and rapid dissemination of insulin . It has been indicated that there is a functional interdependency between IMECs and islet β cells which possibly through secretion of humoral regulatory factors, productions of basement membrane components, and cell‐cell contact‐dependent mechanisms . Meanwhile, IMECs in islet microcirculation interact with various types of cells such as islet pericytes and organ cells namely islet β cells.…”
Section: Introductionmentioning
confidence: 99%
“…6 It has been indicated that there is a functional interdependency between IMECs and islet β cells which possibly through secretion of humoral regulatory factors, productions of basement membrane components, and cell-cell contact-dependent mechanisms. 7 Meanwhile, IMECs in islet microcirculation interact with various types of cells such as islet pericytes and organ cells namely islet β cells. In addition, IMECs contact with ECM components and expose in growth factors and cytokines secreted by their adjacent cells.…”
Section: Introductionmentioning
confidence: 99%